1992
DOI: 10.1111/j.1574-6968.1992.tb05916.x
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneity of peripheral blood monocyte populations in human immunodeficiency virus-1 seropositive patients

Abstract: Monocytes from human immunodeficiency virus (HIV) patients have an increased heterogeneity of phenotype and function. In a study of 120 HIV patients we have demonstrated that they have normal monocyte differential counts but that with progression of the disease an increasing proportion of monocytes show phenotypic and functional evidence for activation or maturation. A proportion of the monocytes are larger, with increased expression of CD11b, HLA‐DR, CD45 and CD16. Concomitantly there was increased expression… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
10
0

Year Published

1995
1995
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 40 publications
2
10
0
Order By: Relevance
“…In addition, higher surface levels of Siglec-1 on monocytes correlate with immune activation as the treatment of these cells with IFNs or bacterial compounds such as lipopolysaccharide increases the surface amount of this type-I lectin. This is consistent with the condition of chronic inflammation and immune activation induced by the presence of HIV-1 viremia that also triggers the expansion of a subset of CD14 pos /CD16 pos -activated monocytes (54, 78, 8184). Hence, although having different kinetics during the course of HIV-1 infection, both the expressions of Siglec-1 and Siglec-7 are greatly influenced by viral replication and can be used as clinical tools to identify and monitor acute and chronic clinical stages of the infection.…”
Section: Kinetics Of Siglecs During the Course Of Hiv-1 Infectionsupporting
confidence: 85%
“…In addition, higher surface levels of Siglec-1 on monocytes correlate with immune activation as the treatment of these cells with IFNs or bacterial compounds such as lipopolysaccharide increases the surface amount of this type-I lectin. This is consistent with the condition of chronic inflammation and immune activation induced by the presence of HIV-1 viremia that also triggers the expansion of a subset of CD14 pos /CD16 pos -activated monocytes (54, 78, 8184). Hence, although having different kinetics during the course of HIV-1 infection, both the expressions of Siglec-1 and Siglec-7 are greatly influenced by viral replication and can be used as clinical tools to identify and monitor acute and chronic clinical stages of the infection.…”
Section: Kinetics Of Siglecs During the Course Of Hiv-1 Infectionsupporting
confidence: 85%
“…allergy, hyper-IgE syndrome, Hodgkin lymphoma, trauma, sepsis, and transplantation), most of which are characterized by elevated Th2 and IgE re-sponses (15, 36 -38). As specified above, elevated levels of PGE 2 have also been reported in individuals infected with HIV-1 (27)(28)(29)(30) and it has been postulated that this may contribute to the immunosuppressive state seen in such virally-infected patients (39). The mechanism(s) responsible for the enhanced prostaglandin formation is still undefined.…”
mentioning
confidence: 98%
“…A marked increase in PGE 2 production is generated in response to a variety of immunological stimuli including interleukin (IL)-1, tumor necrosis factor-␣ (TNF-␣), antigen-antibody complexes, and lipopolysaccharide (15). Moreover, production of PGE 2 has been shown to be induced by infection with several pathogens such as Leishmania donovani (16), Leishmania major (17), Entamoeba histolytica (18,19), Pseudomonas aeruginosa (20,21), Staphylococcus epidermidis (22), Mycobacterium avium (23), herpes simplex virus type 1 (24), coxsackie virus (25), respiratory syncytial virus (26), and HIV-1 (27)(28)(29)(30). PGE 2 has been implicated in decreasing T-cell proliferation, IL-2 production, and IL-2 receptor expression (15,(31)(32)(33)(34)(35).…”
mentioning
confidence: 99%
“…Our results confirm previous reports by others demonstrating increased expression of CD16 by monocytes of HIV-1-seropositive patients. 21,[37][38][39][40][41][42] Further, we have demonstrated that monocyte CD23 directly and significantly correlated with monocyte CD16 expression, indicating that monocytes of AIDS patients express increased levels of both CD23 and CD16. Since monocyte CD23 and CD16 are activation markers of monocytes that are seen in a variety of settings, including allergic and inflammatory states, 1-12,37-42 the identification of increased monocyte CD23 and CD16 may further characterize the activated population of monocytes in AIDS, and may help to explain the altered monocyte-macrophage functions that play an important role in the immunopathogenesis of AIDS.…”
Section: Discussionmentioning
confidence: 97%
“…20 Although this observation suggests a role for monocyte CD23 in HIV-1 disease in vitro, to our knowledge whether monocytes of HIV-1-seropositive patients express CD23 in vivo is unknown. Since peripheral blood monocytes of AIDS patients express phenotypic and functional changes characteristic of an activated or differentiated population, 21,22 it is also possible that they may express increased CD23. Further, since IgE, 23 IL-4, or IFN-g 1,2,4-6 increase monocyte CD23 expression in cultures of healthy human monocytes, and IL-10 suppresses its expression, 24,25 changes in levels of soluble factors in serum/plasma such as IgE or cytokines (IFN-g, IL-4, and IL-10) may alter monocyte CD23 expression during the course of HIV-1 disease.…”
Section: Introductionmentioning
confidence: 98%